Effect of nutrient media and initial biomass on growth rate and nutrient uptake of sargassum spinuligerum(Sargassaceae, phaeophyta) - Hoang, T.; Fotedar, Ravi; O Leary, M. (Scientific and Technical Research Council of Turkey - TUBITAK, 2017)
The Sargassum species are prospective candidates for marine culture, but there are a limited number of reports on their nutrient requirements and optimum initial stocking biomass, and nothing is published for Sargassum spinuligerum. This study investigated the effects of three commercially available fertilizers (Hortico, Seasol, and Aquasol) and four initial stocking biomass levels of S. spinuligerum on the growth rate and nutrient uptake capacities for 7 weeks. The results showed that S. spinuligerum could be grown under outdoor conditions with the optimum initial stocking biomass of 15.35 g per 113 L. The different commercial fertilizers significantly influenced the specific growth rate and nutrient uptake rate of S. spinuligerum. Aquasol resulted in a higher specific growth rate than the other commercial fertilizers, with the relative growth rate fluctuating between 0.42 and 1.70 (% per day). Aquasol is recommended as a nutrient supplement to enhance the specific growth rate of S. spinuligerum.